Exploring Human Values in the Epic Ramayana - Piyush Patel; Dharmik Chauhan (Journal of General Education and Humanities, 2025)
This study analyzes the fundamental human values embedded in the Ramayana attributed to Sage Valmiki. As more than a divine narrative, the Ramayana is a moral guide, shaping ethical behavior and societal harmony. The research aims to examine the portrayal of values such as dharma (duty), Satya (truth), karuna (compassion), and seva (selfless service) through key characters and their influence on ethical conduct. A qualitative approach incorporates textual analysis, cultural interpretation, and philosophical inquiry. The study explores how characters like Rama, Sita, Lakshmana, and Ravana exemplify virtues such as righteousness, devotion, sacrifice, and resilience. The findings highlight the timeless relevance of these values in personal, social, and educational contexts, fostering character development and cultural understanding. The Ramayana's moral framework continues to offer ethical guidance across generations, emphasizing the importance of virtue in contemporary life. Through an in-depth analysis of characters and moral dilemmas, this study underscores the epic's role in shaping ethical consciousness. The research concludes that the Ramayana remains a vital source of moral wisdom, promoting ethical integrity and societal cohesion in traditional and modern contexts.